PREDICTION OF HEPATIC FIBROSIS PROGRESSION RATE IN CHRONIC HEPATITIS C ON THE BASIS OF CLINICAL AND GENETIC SIGNS - Syzova, L.M.; Koval, L.T.; Bodnar, V.A.; Kaydashev, I.P.; Izyumska O.М. (World of Medicine and Biology, 2019)
A cross-sectional study of 166 patients with chronic hepatitis C was carried out. As a result of the analysis, among the 35 possible factors of rapid progression of hepatic fibrosis in chronic hepatitis C, 10 most informative ones were identified: male gender (p=0.005), 1 genotype of HCV (p=0.040), alanine aminotransferase above 3 upper limits of normal (p=0.015), the levels of aspartate aminotransferase, γ-glutamyltranspeptidase and total bilirubin exceeding the upper limit of normal (p=0.000, p=0.000 and p=0.001, respectively), alcohol consumption >40 g/day (p=0.033), chronic cholecystitis and/or pancreatitis (p=0.000), type II diabetes mellitus (p=0.007) and a carriage of the normal genotype (Gln/Gln, Gln/-) of the TLR7 gene (p=0.001). In order to optimize the prognostication of the affiliation of a patient with chronic hepatitis C to the risk group of rapid progression of hepatic fibrosis there were proposed the highly effective mathematical model, developed on the basis of multiple discriminant analysis, exact forecast of which was 82.5 %.